Art, Aesthetics and the Dynamics of Visuality in Ezekiel 23 - Quick, Laura (The journal of Hebrew scriptures, 2021)
This essay explores Ezekiel 23 as a text about art and aesthetics. As an aesthetic response to an artistic endeavour, it argues that the description of Oholibah’s act of viewing must be placed within the context of strategies for verbalizing visual phenomenon in biblical literature. And as a work of art, the carved Chaldean officers must be understood within larger ancient Near Eastern artistic conventions. The convergence of these distinct but related focuses allows us to reassess Oholibah’s act of viewing art and its role in Ezekiel 23.